Genetic ablation of ankrd1 mitigates cardiac damage during experimental autoimmune myocarditis in mice - Rinkūnaitė, Ieva; Šimoliūnas, Egidijus; Alksnė, Milda; Bartkutė, Gabrielė; Labeit, Siegfried; Bukelskienė, Virginija; Bogomolovas, Julius (Biomolecules, 2022)
Myocarditis (MC) is an inflammatory disease of the myocardium that can cause sudden death in the acute phase, and dilated cardiomyopathy (DCM) with chronic heart failure as its major long-term outcome. However, the molecular mechanisms beyond the acute MC phase remain poorly understood. The ankyrin repeat domain 1 (ANKRD1) is a functionally pleiotropic stress/stretch-inducible protein, which can modulate cardiac stress response during various forms of pathological stimuli; however, its involvement in post-MC cardiac remodeling leading to DCM is not known. To address this, we induced experimental autoimmune myocarditis (EAM) in ANKRD1-deficient mice, and evaluated post-MC consequences at the DCM stage mice hearts. We demonstrated that ANKRD1 does not significantly modulate heart failure; nevertheless, the genetic ablation of Ankrd1 blunted the cardiac damage/remodeling and preserved heart function during post-MC DCM.
Gesehen am 08.02.2023